Effects of oyster shell addition on shrimp aquaculture and the dynamic succession of surface biofilm microbial communities - Huang, Xianke; Xiao, Guoqiang; Zhang, Xiang; Teng, Shuangshuang; Li, Min; Cai, Yilong; Chen, Ran; Huang, Xiaolin (Frontiers in Marine Science, 2024)
Introduction In the context of Litopenaeus vannamei aquaculture, the incorporation of oyster shells has proven beneficial for enhancing water quality and the growth conditions of the shrimp. Nonetheless, the specific effects of in-situ water treatment using oyster shells on water quality and shrimp growth, along with the composition and succession dynamics of the microbial community within oyster shell biofilms, have yet to be thoroughly investigated. Methods This study established control, low-concentration, and high-concentration oyster shell addition groups to emulate the in-situ water treatment environment with oyster shells, with the objective of elucidating the impacts of oyster shell addition on the aquaculture setting. Results The results showed that the addition of oyster shells could significantly improve the length (F = 12.248, P = 0.005), weight(F = 138.234, P < 0.001), and survival rate (F = 15.248, P < 0.001) of shrimp, while there were no significant differences in the length (F = -1.233, P = 0.267) and survival rate (F = -2.143, P = 0.076) between the high and low concentration groups. Additionally, oyster shell addition resulted in elevated phosphate levels (F = 74.92, P < 0.001 in Day 70), diminished nitrite levels (F = 5.276, P = 0.031 in Day 56), and increased nitrate concentrations (F = 9.421, P = 0.006 in Day 70). Within the biofilms, the relative abundances of Ruegeria, Tenacibaculum, BD2- 11_terrestrial_group, and Kapabacteriales exhibited significant declines over time, whereas the relative abundance of Nitrospira demonstrated a marked increase, ultimately emerging as the predominant bacterium (Relative abundance 31.8%) in the biofilms during the latter stages of the experiment. Nitrospira also exhibited a notably higher relative abundance in the microbial community of the experimental water group relative to the control group (F = 2.265, P = 0.001). Discussion The biofilm provided conditions for the proliferation of Nitrospira, thereby accelerating the transformation of nitrite into nitrate in the aquaculture system, which subsequently improved the shrimp farming conditions. This research offers valuable insights for the application of oyster shells in shrimp farming and contributes to the theoretical underpinnings necessary for advancing our understanding of the mechanisms through which oyster shell biofilms enhance water quality and foster shrimp health.